Response of sugarcane genotypes to varying planting environments under two distinct agro-climatic zones of Punjab, India - Mishra, Sudhir Kumar; Singh, Jashandeep; Singh, Kuldeep; Singh, Harkanwaljot; Kingra, Pavneet Kaur; Singh, Vikrant; Biswas, Barun (Journal of Sugarcane Research, 2023)
Sugarcane, an important sugar producing crop provides raw materials for sugar industries hence, creates employment for the human population. In India, sugarcane planting has large sowing window starting from autumn (October-November) to spring season (February- March/April). To determine the optimum planting time of sugarcane cultivars, a field experiment was conducted during 2017-18 at two diverse locations (Faridkot and Gurdaspur) of Punjab, in split plot design having three planting dates (February 25th, March 25th and April 25th) in main plots and four sugarcane cultivars (CoPb 91, CoJ 88, Co 0118 and Co 0238) in sub-plots with 3 replications. Results described that the sugarcane crop planted on February 25 produced more tillers that resulted in maximum millable canes (i.e., 113.8 '000 / ha at Faridkot and 107.3 '000 / ha at Gurdaspur, respectively). At both sites, maximum cane yield of 128.4 and 136.3 t / ha was recorded under the February 25 planted crop, which was 15.5 and 18.4 % more than March 25 and 31.2 and 36.9% higher than the April 25 planted crop, respectively. At both locations, the higher cane yield (128.4 and 136.3 t / ha) under February 25 planted crop might be attributed to improved yield parameters such as more millable canes (113.8 and 107.3'000/ha), higher single cane weight (1.2 and 1.4kg) and better quality attributes viz., extraction (55.9 and 56.1%), brix (18.5 and 18.6%), sucrose (16.5 and 16.8%), purity (89.3 and 90.5%) and commercial cane sugar (11.5 and 11.8%). Stable sugarcane yield of Co 0238 was obtained in agro climatic zone II, while CoJ 88 was very uniform in agro climatic zone IV, so these varieties can be selected for cultivation in respective agro climatic zones of Punjab. Therefore, variety CoJ 88 is suitable for Faridkot and Co 0238 for Gurdaspur. In contrast, Co 0118 showed very inconsistent performance at both regions.